Instant Hydrogelation Inspired by Inflammasomes. (24th May 2017) - Wang, Huaimin; Feng, Zhaoqianqi; Lu, Alvin; Jiang, Yujie; Wu, Hao; Xu, Bing
Abstract: Based on the recent near‐atomic structures of the PYRIN domain of ASC in the protein filament of inflammasomes and the observation that the active form of vitamin B6 (pyridoxal phosphate, P5P) modulates the self‐assembly of ASC, we rationally designed an N‐terminal capped nonapeptide (Nap‐FFKKFKLKL, 1 ) to form supramolecular nanofibers consisting of α‐helix. The addition of P5P to the solution of1 results in a hydrogel almost instantly (about 4 seconds). Several other endogenous small molecules (for example, pyridoxal, folinic acid, ATP, and AMP) also convert the solution of1 into a hydrogel. As the demonstration of correlating assemblies of peptides and the relevant protein epitopes, this work illustrates a bioinspired approach to develop supramolecular structures modulated by endogenous small molecules.